Exploring facilitators and inhibitors of communication in ethnically diverse groups: the experience of academician - A.Manaf, Aini Maznina (2010)
This paper presents what factors are considered as facilitating and inhibiting communication effectiveness in ethnically diverse groups of academic environments. Phenomenological approach which was used to guide the data collection and data analysis of this study is discussed. Drawing on in-depth interviews with 40 researchers who engaged in small group research activities of five public and private universities in Malaysia, language similarity, exposure to other ethnic groups, open communication climate, teamwork spirit, individuals’ upbringing are among factors that facilitate good communication among academic members. On the other hand, cultural difference, age gap, closed communication, individuals’ competitive behaviour, and lack of socialisation activities are among factors that inhibit effective communication in the ethnically diverse group. This article concludes that individual members and groups themselves are equally important for effective communication in an ethnically diverse group.